Analisis Kartu Indonesia Pintar Melalui Perspektif George C. Edwards III di Kecamatan Gringsing - Sumarno, Sumarno; Nurcholis, Hanif; Rina Herawati, Augustin (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
This study aims to examine the implementation of the Program Indonesia Pintar (PIP) in Gringsing District, Batang Regency. Based on field findings, the implementation of the PIP program in this area shows several problems, including mistargeting of beneficiaries, suboptimal implementation processes, and low program effectiveness at the elementary, junior secondary, and senior secondary education levels. The study focuses on four main factors of policy implementation according to George C. Edwards III’s theory—communication, resources, disposition, and bureaucratic structure—as indicators of implementation success. The research employs a qualitative approach using data triangulation techniques, including observation, documentation, and in-depth interviews. The findings indicate disparities in the distribution of PIP assistance. From the perspective of George C. Edwards III, four factors contribute to these disparities: (1) communication, (2) resources, (3) disposition, and (4) bureaucratic structure. The study concludes that improving PIP implementation requires an integrated approach encompassing strengthened policy communication, enhanced capacity of implementers and beneficiaries, bureaucratic procedure reform, and integration of assistance programs with efforts to improve educational quality. With these improvements, the Program Indonesia Pintar is expected to have a more significant impact on educational equity and quality in Gringsing District.